The modern concept of intensive therapy of coagulopathy, which is complicate polytrauma and shock - V.I. Cherniy (Клінічна та профілактична медицина, 2019)
The statute presents the fourth edition (The European guideline on management of major bleeding and coagulopathy following trauma: fourth edition, 2016) of European recommendations on the treatment of severe blood loss and coagulopathy caused by injury. More than 50% of all trauma patients with a fatal outcome die within 24 hours after injury. After hospitalization in a third of patients with trauma, the bleeding is coagulopathic. They significantly increase the risk of multiple organ failure and death compared with patients with similar trauma in the absence of coagulopathy. Early acute coagulopathy associated with traumatic injury is multifactorial: 1) hemorrhage induced shock; 2) tissue damage with the release of tissue thromboplastin and the development of thrombinemia; 3) activation of anticoagulant and fibrinolytic systems. The severity of coagulation disorders is determined by the influence of environmental factors, metabolic disorders (acidosis, hypothermia, tissue hypoperfusion and consumption coagulopathy) and therapeutic strategy. Coagulopathies can be associated with trauma to the brain, liver, and patient's individual characteristics, which include age, heredity, comorbidities, and medication, especially oral anticoagulants. Coagulation monitoring (internationally normalized ratio (INR) and APTT), characterizes only the beginning of the 2nd phase of blood coagulation, and represents the generation of only the first 4% of thrombin. Therefore, the performance of a normal coagulogram may be normal, although the general condition of the blood coagulation system is pathological. Late diagnosis of traumatic coagulopathy may affect the outcome. A new concept of reanimation of patients with massive bleeding has been presented, the immediate introduction of coagulation components (RBC, native plasma and platelets in a 1: 1: 1 ratio), tranexamic acid, fresh frozen plasma, fibrinogen concentrate, desmopressin, prothrombin complex concentrate, recombinant activated coagulation factor VII (rFVIIa). Currently, the issue of using fresh whole blood for resuscitation in case of injury and massive blood loss is relevant.